Efektivitas Storytelling dalam Meningkatkan Minat Baca Anak: Studi Kasus Program Kejar Baca di Perpustakaan Cinta Baca Medan - Saiful, Nurhaliza (Jurnal Pustaka Ilmiah, 2024)
Based on the results of the Program for International Student Assessment (PISA) survey in 2022, Indonesia's score has decreased, especially in reading ability scores. Indonesia's reading score in PISA 2018 was 371 while PISA 2022 dropped to 359. From the initial field observations, the author found that there are literacy activities in the form of storytelling at Cinta Baca Library Medan. The activity is routinely carried out once a week to increase children's interest in reading. This study aims to examine and observe in depth how storytelling activities in the Kejar Baca Program can be implemented effectively in increasing children’s interest in reading at the Medan Cinta Baca Library.This research uses a qualitative descriptive method with a case study type. Data collection techniques in this study used observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model analysis technique which consists of 3 activities, namely data reduction, data display, and verification or conclusion. Based on the results of interviews with informants and direct observation, storytelling can be said to be effective in increasing children's interest in reading. This can be seen from children who are enthusiastic about the story and active in responding to questions and discussions about the story. Indirectly, children have taken part in reading the story. Some children who participated in storytelling became active in visiting the library and borrowing reading books. Poor environment and lack of motivation are challenges in implementing storytelling activities in the library. In addition, age changes and other activities are also unavoidable challenges.